Prosopis juliflora biochar-based hybrid composites: Mechanical property assessment and development prospects - Sundarakannan Rajendran; Vigneshwaran Shanmugam; Shankar Sanjeevi; Yo-Lun Yang; Uthayakumar Marimuthu; Geetha Palani; Arumugaprabu Veerasimman; Herri Trilaksana (Cleaner Engineering and Technology)
This study investigates the incorporation of biochar derived from invasive Prosopis Juliflora wood as a filler in jute fibre-reinforced epoxy composites at varying weight fractions (5 %, 10 %, 15 %, and 20 % wt). Mechanical evaluations comprised tensile, flexural, impact, and hardness tests, in addition to water absorption assessments. The composite containing 10 % weight biochar exhibited superior performance compared to conventional composites, demonstrating a tensile strength of 49 MPa, a hardness of 79, and an impact strength of 63 J/m. A peak flexural strength of 90 MPa was observed at 15 % wt. Biochar. The findings indicate the potential of biochar sourced from Prosopis Juliflora for sustainable composite materials applicable in the aerospace, automotive, and construction industries.